2017
DOI: 10.24925/turjaf.v5i3.226-230.994
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Seaweed Doses on Yield and Nutritional Values of Hydroponic Wheatgrass Juice

Abstract: This research was conducted to determine the effects of different seaweed doses on yield and nutritional values of hydroponic wheatgrass (Triticum aestivum L.) juice in the climatization chamber of Karabuk University, Eskipazar Vocational School, Department of Crop and Animal Production between the dates of 15. 01.2015 and 15.06.2015. In the research, four different seaweed doses (Control; 0, D1; 150, D2; 300, D3; 450 and D4; 600 ppm) and control were applied to irrigation water and their effects on the conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The effects on plant yield, seed rate, plant and grass yield, grass juice yield and pH, plant height and root length were investigated. It was stated that the highest plant, grass and grass juice yields and plant height values were obtained from D1 application, while the highest root length values were obtained from D1 and D3 applications [19]. In our study, the highest root and plant length were obtained from the barley grass juice application, and the lowest values were obtained from the wheat grass juice application.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…The effects on plant yield, seed rate, plant and grass yield, grass juice yield and pH, plant height and root length were investigated. It was stated that the highest plant, grass and grass juice yields and plant height values were obtained from D1 application, while the highest root length values were obtained from D1 and D3 applications [19]. In our study, the highest root and plant length were obtained from the barley grass juice application, and the lowest values were obtained from the wheat grass juice application.…”
Section: Discussionsupporting
confidence: 44%
“…In our study, the highest root and plant length were obtained from the barley grass juice application, and the lowest values were obtained from the wheat grass juice application. In another study conducted in hydroponic environment, the yield and nutritional values of barley, wheat and corn grass juice were examined, plant height and root length were examined and it was determined that the highest root length belonged to the corn plant [20]. Karaman et al [21] investigated the effects of essential oil doses obtained from lavender plant on culture and foreign plants and reported that with the increase of lavender oil doses, germination and seedling properties decreased.…”
Section: Discussionmentioning
confidence: 99%
“…It should be considered that high yield in grass juice of quality wheat cultivars can be obtained via some cultural practices such as carbon dioxide (Karaşahin, 2015), seaweed treatments (Karaşahin, 2017), adequate cutting length (Ergün, 2011;Agrawal et al, 2015), or suitable cutting time (Kulkarni, 2006;Kardas and Durucasu, 2014;Lae and Oo, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In modern agriculture, the current trend is to explore for breakthrough technology that would have chemical reduction inputs while maintaining yields [17][18][19]. KD Foliar, a locally made seaweed fertilizer created by SPAMAST and generated from Kappaphycus alvarezii seaweed, was discovered to contain much plant growth and development requires nutrients and minerals [20][21][22][23][24][25][26]. This study compared the growth increase of tissue cultured Abaca to conventional fertilizer and biostimulant using the innovative product.…”
Section: Introductionmentioning
confidence: 99%